DESIGN AND STUDY OF TIME RELAYS - Kirillova, Olga; Markov, Alexandr (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
By operation of security circuits and automatic equipment it is often required to create time delay between actuating of two or several devices. In case of automation of technological processes there can also be a need to make operations in a certain temporal sequence. Automated systems of industrial production rather often use electric drives (adjustable) which consist relays (time elements), they allow exercising control on the given algorithm. It can be algorithms of serial switching on or implementation of start of the electric drive in strict sequence including a starting element. The time relay is used in cases when it is necessary to perform automatically some operation not right after appearance of the managing director of a signal, and through the set period. For creation of a time delay there are devices called time relays [1].